AC motor position control using fuzzy logic controller - Wan Nur Azhani, W. Samsudin (2007)
Motor position control is very important in rotating machinery applications. There are many applications that have been developed based on motor position control theory, such as crane controller, lift and conveyor. The position control of an ac motor is very difficult to be implemented by using traditional control techniques, as it requires a very complex mathematical model. The purpose for this project is to describe the research on fuzzy logic controller (FLC) design based on programmable logic controller (PLC) in order to control the position of an ac motor of University Malaysia Pahang (UMP) mini conveyor. By using FLC, the conveyor will stop at the desired point set by the user with minimum error. The model of the PLC that has been used in this project is OMRON CQM1H-CPU51. Before the controller was developed, numbers of simulations were done using MATLAB Fuzzy Logic Toolbox and SIMULINK. There are three rules that have been implemented in this project, which used three membership functions. Based on the simulation, it can be concluded that the system which has many rules in the fuzzy logic controller produced better response compared to the system using a few rules.